2018
DOI: 10.48550/arxiv.1804.03450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

End of Potential Line

John Fearnley,
Spencer Gordon,
Ruta Mehta
et al.

Abstract: We introduce the problem EndOfPotentialLine and the corresponding complexity class EOPL of all problems that can be reduced to it in polynomial time. This class captures problems that admit a single combinatorial proof of their joint membership in the complexity classes PPAD of fixpoint problems and PLS of local search problems. EOPL is a combinatorially-defined alternative to the class CLS (for Continuous Local Search), which was introduced in [16] with the goal of capturing the complexity of some well-known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In a recent paper, Sotiraki et al [67] identified the first natural problem for the class PPP, the class of problems whose totality is established by an argument based on the pigeonhole principle. For the class CLS, both Daskalakis et al [21] and Fearnley et al [27] identified complete problems (two versions of the Contraction Map problem, where a metric or a meta-metric are given as part of the input). In the latter paper, the authors define a new class, namely EOPL (for "End of Potential Line"), and show that it is a subclass of CLS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, Sotiraki et al [67] identified the first natural problem for the class PPP, the class of problems whose totality is established by an argument based on the pigeonhole principle. For the class CLS, both Daskalakis et al [21] and Fearnley et al [27] identified complete problems (two versions of the Contraction Map problem, where a metric or a meta-metric are given as part of the input). In the latter paper, the authors define a new class, namely EOPL (for "End of Potential Line"), and show that it is a subclass of CLS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they show that two well-known problems in CLS, the P-Matrix Linear Complementarity Problem (P-LCP), and finding a fixpoint of a piecewise-linear contraction map (PL-Contraction) belong to the class. The End of Potential Line problem of [27] is closely related to the End of Metered Line of [39].…”
Section: Introductionmentioning
confidence: 99%
“…Its corresponding computational problem Contraction, is to find a fixed point of a given contraction map. Some versions of Contraction have been shown complete for CLS, a subclass of PPAD [11,12,16]. The search for Brouwer fixpoints (including discretised versions of Brouwer functions) is PPAD-complete for most variants of the problem [29,7], which is why we say the HBT is "Brouwer-like".…”
Section: Other Related Workmentioning
confidence: 99%